Mortality Among Hispanic Drug Users In Puerto Rico - Robles, Rafaela R.; Matos, Tomás D.; Colón, Héctor M.; Sahai, Hardeo; Reyes, Juan C.; Marrero, Amalia; Calderón, José M. (Puerto Rico Health Sciences Journal, 2011)
see manuscript